2012
DOI: 10.5897/ajfs12.014
|View full text |Cite
|
Sign up to set email alerts
|

Consumer acceptability of four products made from beta-carotene-rich sweet potato

Abstract: Beta-carotene-rich (orange-fleshed) sweet potato is one of a few new crops, which is an excellent source of energy and important nutritive substances that can contribute to improve the nutrient status of communities. The crop is being promoted in the developing world as a source of provitamin A towards alleviating vitamin A deficiency (VAD). The purpose of the study was to determine the consumer acceptability of four products made from β-carotene-rich sweetpotato namely chips, doughnuts, juice and sweet potato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…We can conclude that consumption of sweet potato leaves rich in dietary fibre, vitamins and antioxidants in the form of carotenoids would be useful in neutralizing free radicals in the body and hence reduce the harmful effects of oxidative stress (Teow et al, 2007). The addition of G. africanum to sweet potato leaves was acceptable particularly because its appearance and the mixture and preparation did not alter the organoleptic attributes of the sauce (Laurie and Van Heerden, 2012). A possible reason for 33% of the panellists being neutral/indifferent regarding the taste of the sauce is because it was the first time of tasting a G. africanumbased sauce of a slightly different flavour from what they are accustomed to.…”
Section: Discussionmentioning
confidence: 99%
“…We can conclude that consumption of sweet potato leaves rich in dietary fibre, vitamins and antioxidants in the form of carotenoids would be useful in neutralizing free radicals in the body and hence reduce the harmful effects of oxidative stress (Teow et al, 2007). The addition of G. africanum to sweet potato leaves was acceptable particularly because its appearance and the mixture and preparation did not alter the organoleptic attributes of the sauce (Laurie and Van Heerden, 2012). A possible reason for 33% of the panellists being neutral/indifferent regarding the taste of the sauce is because it was the first time of tasting a G. africanumbased sauce of a slightly different flavour from what they are accustomed to.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, limited attention has been given to improving sensorial quality of malted complementary foods. Considering the fact that acceptability of food is largely driven by sensory appeal compared to nutritional quality (Laurie & Van Heerden, 2012), the observed negative sensorial effect is a potential factor that should be critically considered in future attempts to improve the efficacy of the traditional malting technology for enhancing bioavailability of nutrients from plant‐based foods. A major limitation of this study is that bioavailability of iron and zinc was assessed after malting and roasting treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Sweet potato (Ipomoa batatas L.) is one of the most important albeit underutilised (Ali et al, 2012) crops and source of essential nutrients, primarily vitamin A (in the orange-fleshed varieties) (Kulembeka et al, 2004;Agili et al, 2012;Laurie & Van Heerden, 2012). Consumers are increasingly conscious about their health and have since started to consider the nutritional benefits, disease prevention, and health-promoting properties of foods.…”
Section: Introductionmentioning
confidence: 99%
“…Human consumption of the other plant parts such as the leaves can also improve its nutritional value. A recent study by Laurie & Van Heerden (2012) reported good acceptability of beta-carotene-rich sweet potato leaves as a leafy vegetable, which indicated the need to promote consumption of leaves. According to Islam (2006), sweet potato leaves have largely been neglected except for partial use as livestock feed.…”
Section: Introductionmentioning
confidence: 99%